STRATEGI KOMUNIKASI PEMASARAN BAND INDIE SCARHEAD BARRICADE - Adam, Sigit Tri Putra (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2018)
The emergence of indie labels in Palu City requires each musician to produce and sell his works using production patterns that are self-released without any major label interference. This is a major challenge for the Scarhead Barricade band to be able to maintain its band in the indie music competition industry in the Palu City. The theory used in this study is the theory of Integrated marketing communication (IMC) from Richard J. Semenik. The research method used in this study is a descriptive research method that describes or presents marketing communication strategies carried out by the Scarhead Barricade band for the period of 2016 - 2017. Data collected through observation, in-depth interviews and documentation. The data analysis technique used is the Miles and Huberman model which consists of four components, namely data collection, data reduction, data presentation and conclusion drawing. The results showed that in the indie music competition in Palu City, the Scarhead Barricade band, conducted a marketing communication strategy by combining promotional tools or commonly called the Promotion mix. In this promotion mix, the Scarhead Barricade band uses publicity through print and online media. Advertising by creating posters, stickers, pamphlets and also using radio. Internet marketing done by using social media and websites. Personal selling is done by setting up a stand with a sales person during a music festival. Scarhead Barricade's sales promotion is done by providing products in the form of bundle packages and releasing singles via online for free. In carrying out this marketing communication Scarhead Barricade uses more internet marketing as a promotional media, besides being cheap and easy to use this media is very effective to boost product sales.